2022
DOI: 10.1542/peds.2022-059009
|View full text |Cite
|
Sign up to set email alerts
|

Six-Month Outcomes of Infants Born to People With SARS-CoV-2 in Pregnancy

Abstract: OBJECTIVES: To assess the 6-month incidence of laboratory-confirmed severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection, postnatal care, hospitalization, and mortality among infants born to people with laboratory-confirmed SARS-CoV-2 infection during pregnancy by timing of maternal infection. METHODS: Using a cohort of liveborn infants from pregnancies with SARS-CoV-2 infections in the year 2020 from 10 Uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…Of these, 1491 were discharged to another facility, discharged to hospice, or deceased within a day of birth; these newborns were included for analysis without imputing a higher-level nursery. For the remaining 6165 newborns, we backfilled Level III or higher care when [1] they were born ≤35 weeks' gestation (1876/6165) or [2] had a billing record that indicated likely ICU-level care (e.g., caffeine, surfactant, total parenteral nutrition, furosemide, lorazepam, nitric oxide, umbilical catheter) (4289/ 6165).…”
Section: Measures and Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, 1491 were discharged to another facility, discharged to hospice, or deceased within a day of birth; these newborns were included for analysis without imputing a higher-level nursery. For the remaining 6165 newborns, we backfilled Level III or higher care when [1] they were born ≤35 weeks' gestation (1876/6165) or [2] had a billing record that indicated likely ICU-level care (e.g., caffeine, surfactant, total parenteral nutrition, furosemide, lorazepam, nitric oxide, umbilical catheter) (4289/ 6165).…”
Section: Measures and Outcomesmentioning
confidence: 99%
“…While Coronavirus disease 2019 (COVID-19) in newborns is uncommon, studies have reported 0.4-3.6% of infants born to mothers with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection during pregnancy test positive during the birth hospitalization or within 14 days of birth, depending on methodology, population, and period of the study [1][2][3]. Findings from the period when wild-type SARS-CoV-2 virus was predominant (March-December 2020) showed that late preterm and term newborns (≥34 gestational weeks) with COVID-19 had an increased risk of neonatal intensive care unit (ICU) admission and early preterm newborns (<34 gestational weeks) with COVID-19 had an increased risk of invasive ventilation support [4].…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary studies during the first few months of the pandemic noted decreases in breastfeeding and EBF from pre-pandemic rates [12]. Similarly, patients with cases of SARS-CoV-2 diagnosed less than two weeks prior to delivery in 2020 were found to be less likely to initiate breastfeeding at all [15]. Given the uncertainties toward the impact of COVID-19 on newborns during this period, these findings may be attributed to safety concerns at the beginning of the pandemic.…”
Section: Discussionmentioning
confidence: 96%
“…SET‐NET constitutes an adaptable mother–infant surveillance network, with general variables consistent across conditions, as well as modular data elements that allow for expansion to novel conditions (Woodworth et al, 2021). Most recently, SET‐NET data were used to describe SARS‐CoV‐2 testing patterns and positivity rates among neonates born to pregnant persons with SARS‐CoV‐2 infection during pregnancy, as well as infant outcomes through 6 months of age (Olsen et al, 2022; Gosdin et al, in press). During 2022–2023, CDC will fund five jurisdictions (Iowa, Minnesota, New Jersey, New York, and Utah) to pilot cCMV surveillance through SET‐NET.…”
Section: Discussionmentioning
confidence: 99%